1991
DOI: 10.3109/02713689109013878
|View full text |Cite
|
Sign up to set email alerts
|

The influence of epidermal growth factor on cat corneal endothelial wound healing

Abstract: Using standardized freeze wounds in cat corneas, we tested the efficacy of human recombinant Epidermal Growth Factor (EGF) to promote endothelial healing when solubilized in either phosphate buffered saline (PBS), 1% methylcellulose (MC), or sodium hyaluronate (NaHA), in final intraocular doses ranging from 2 micrograms to 100 micrograms of EGF. After 6 or 7 days' healing, animals were humanely sacrificed and corneal tissues were fixed and stained for light microscopy and computation of remaining wound areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…HA has been used in other systems to deliver growth factors, including the eye. Rich et al 39 showed improved wound healing in cat eyes treated with EGF solubilized in HA. Similarly, Raphael et al .4°i n 1993 showed that, after an endothelial cell injury, a single intraocular injection of EGF formulated in sodium hyaluronate significantly enhanced multiple parameters that are closely related to improved endothelial cell regeneration .…”
Section: Wound Repair and Regeneration January-march 7997mentioning
confidence: 98%
“…HA has been used in other systems to deliver growth factors, including the eye. Rich et al 39 showed improved wound healing in cat eyes treated with EGF solubilized in HA. Similarly, Raphael et al .4°i n 1993 showed that, after an endothelial cell injury, a single intraocular injection of EGF formulated in sodium hyaluronate significantly enhanced multiple parameters that are closely related to improved endothelial cell regeneration .…”
Section: Wound Repair and Regeneration January-march 7997mentioning
confidence: 98%
“…These proteins constitute less than 0.4% of the protein in MGF-I1 but retain greater than 90% of MGF-II's capacity to stimulate DNA synthesis in cultured AKR-2B cells and rabbit stromal fibroblasts(22).Together, the current cell culture data, the 1982 report, and the results of our more recent fractionation studies indicate that only a limited amount of the R-MGF prepa-ration could be EGF: on the order of 10 to 500 n g / d at the 2.5 to 100 pg/ml MGF dosages used in this study.Other studies in this laboratory have shown that final aqueous dosages of EGF ranging from 3.3 to 167 p g / d , based on an anterior chamber volume of 600 pl in the cat, did not stimulate endothelial wound healing when administered in PBS. Even when EGF was administered in the viscoelastic agent hyaluronic acid, dosages of pure EGF ranging from 3.3 to 50 pg/ml were required to accelerate wound closure(23).The possibility exists that low levels of EGF may be interacting with other components of R-MGF to stimulate the wound healing seen in the present study. Alternatively, the kallikreins identified in MGF-I and -11 (21) along with the kallikrein activities identified in MGF-I11 and -1V…”
mentioning
confidence: 73%